Essentials of modern business statistics with Microsoft® Office Excel® - Anderson, David R. (David Ray), 1941- author (Cengage Learning, 2018)
The purpose of Essentials of Modern Business Statistics with Microsoft® Office Excel® is to give students, primarily those in the fields of business administration and economics, a conceptual introduction to the field of statistics and its many applications.